Efficacy of NSAIDs for the prevention of acute mountain sickness: a systematic review and meta-analysis - Anil Pandit; Paras Karmacharya; Ranjan Pathak; Smith Giri; Madan R. Aryal (Greater Baltimore Medical Center, 2014)
Background: Acute mountain sickness (AMS) can occur in anyone going to a high altitude. Non-steroidal anti-inflammatory drugs (NSAIDs) have been studied for the prevention of AMS with mixed results. In this systematic review, we analyze all existing data on the use of NSAIDs to prevent AMS using the Lake Louise Scoring System (LLSS) in different randomized clinical trials (RCTs). Methods: Electronic literature searches for relevant studies were identified through MEDLINE, EMBASE, SCOPUS, and Cochrane library up to June 2013. RCTs involving NSAIDs compared to placebo in patients undergoing ascent to a height of at least 3,800 m were included. Odds ratios (OR) were calculated and combined using fixed-effect model meta-analysis if I 2=0%. Differences between groups were calculated using the inverse variance of the standard mean differences. Between-study heterogeneity was assessed using the I 2 statistics. Results: In three clinical trials involving 349 patients, AMS using LLSS occurred in 26.92% of patients on NSAIDs and 43.71% on placebo (OR 0.43; CI [confidence interval] 0.27-0.69, I 2=0%, p=0.0005), NNT=6. Minor outcome of end point Spo2 was not significant in the two groups (IV=0.74; 95% CI −0.20-1.69, I 2=81%, p=0.12). Similarly, a change in Spo2 from baseline was also not significant in the two groups (IV=0.05; 95% CI −0.28-0.37, I 2=44%, p=0.78). Conclusion: NSAIDs might be a safe and effective alternative for the prevention of AMS. However, further larger population studies and studies comparing NSAIDs to acetazolamide and dexamethasone in the future may provide further data to its relative efficacy.